The Role of Extracurricular Organizations in Fostering Social Behavior of Students - Utami, Selvia; Ananda, Asti; Irfadillah, Irfadillah; Bahar, Alfiana; Agustina, Agustina (DIDAKTIKA, 2024)
This thesis discusses the role of extracurricular organizations in growing the social behavior of students at MTs AR RAHMAN KAJU, Sibulue District, Bone Regency. The purpose of this study was to determine the role of extracurricular organizations in MTs AR RAHMAN KAJU, to find out how to grow the social behavior of students at MTs AR RAHMAN KAJU, to find out the barriers and support for students in social behavior? The research method used is field research through a management science approach, a pedagogic approach, and a sociological approach using observation, interview, and documentation techniques. The data obtained were analyzed using descriptive qualitative analysis with 3 stages, namely the data reduction stage (data reduction), data presentation (data display) and the conclusion stage (verification). The results of the study indicate that extracurricular activities at MTs AR RAHMAN KAJU still need to be improved and maximized, such as involvement in extracurricular groups and working on assignments given by extracurricular coaches and assignments given by educators in the classroom. Where students have different characters, there are students who are easy to manage, there are also students who are difficult to manage, as some students like to be given assignments and complete without being asked, but some students don't like being given assignments and are always looking for reasons not to do it. And students who violate the rules in extracurricular activities are given educational sanctions, where character building through extracurricular activities still requires students to need help and direction from extracurricular coaches or educators. It can be understood that the role of extracurricular organizations at MTs AR RAHMAN KAJU is good but still needs to be improved or still needs to be fostered to get maximum results. students are always guided to get used to social behavior but the rules that have been set at school students still often violate them both in terms of clothing and cleanliness as for obstacles for parents in shaping children's social behavior, children are difficult to regulate and the influence of friends hang out with children too many activities in the school. outside with friends compared to study time such as playing more games and smoking cigarettes and the support given by parents to children's social behavior, namely always providing monitoring or supervision in the uss of social media.